METHODS FOR THE PREVENTION OF INSOLVENCY OF COLORECTAL ANASTOMOSIS AT RESTORING CONTINUITY OBSTRUCTIVE BOWEL AFTER RESECTION - V. S. Groshilin; Yu. L. Naboka; M. I. Sultanmuradov; A. D. Haragezov (Медицинский вестник Юга России, 2014)
Purpose: To improve the results of restorative surgical treatment of patients after obstructive resection of the distal colon. Materials and methods: The analysis of surgical treatment results at 30 patients who had operations on restoring the intestinescontinuity after obstructive resections of distal segments of a large intestine has been carried out (operations of Hartmann type).Results: The algorithm of defining the timeframes and way of operations on restoring large intestine continuity has beendeveloped. The priority value in the choice of length and functional condition of a postcolostomic stump medical tactics, changesof its microflora, as well as function of the rectal locking apparatus has been established.Summary: The obtained results (93,3% of favorable outcomes without complications) allow to recommend the offered tactics(including preventive methods of anastomosis incompetence and transanal decompression of the intestines) for wide practicalapplying.